Hyperspectral imaging for the detection of plant pathogens in seeds: recent developments and challenges - Ferreira, Luciellen da Costa; Carvalho, Ian Carlos Bispo; Jorge, Lúcio André de Castro; Quezado-Duval, Alice Maria; Rossato, Maurício (Frontiers in Plant Science, 2024)
Food security, a critical concern amid global population growth, faces challenges in sustainable agricultural production due to significant yield losses caused by plant diseases, with a multitude of them caused by seedborne plant pathogen. With the expansion of the international seed market with global movement of this propagative plant material, and considering that about 90% of economically important crops grown from seeds, seed pathology emerged as an important discipline. Seed health testing is presently part of quality analysis and carried out by seed enterprises and governmental institutions looking forward to exclude a new pathogen in a country or site. The development of seedborne pathogens detection methods has been following the plant pathogen detection and diagnosis advances, from the use of cultivation on semi-selective media, to antibodies and DNA-based techniques. Hyperspectral imaging (HSI) associated with artificial intelligence can be considered the new frontier for seedborne pathogen detection with high accuracy in discriminating infected from healthy seeds. The development of the process consists of standardization of methods and protocols with the validation of spectral signatures for presence and incidence of contamined seeds.Concurrently, epidemiological studies correlating this information with disease outbreaks would help in determining the acceptable thresholds of seed contamination. Despite the limiting factors of equipment high costs and the need of interdisciplinary collaboration, it would be expected that health seed certifying programs and seed suppliers would be benefited with HSI technique in the near future.